Adaptive changes in phosphate uptake by the fungus Neurospora crassa in response to phosphate supply. - Beever, R E (1977)
The phosphate uptake rate of Neurospora crassa germlings growing exponentially in media containing phosphate at concentrations between 10 mM and 50 micronM was virtually constant. The uptake characteristics of these germlings were studied in detail assuming the simultaneous operation of two uptake systems, one of low affinity and one of high affinity. The Km of the low-affinity system was constant after growth at phosphate concentrations greater than 1 mM but became progressively lower as the concentration was reduced below 1 mM. In contrast, the Km of the high-affinity system was independent of the phosphate concentration of the growth medium. The Vmax of each system was highest after growth at low phosphate concentrations. As the phosphate concentration was increased to a maximum of 100 mM, the Vmax of the low-affinity system fell gradually, whereas that of the high-affinity system at first fell rapidly but then reached a constant minimum value at concentrations of 2.5 mM and higher. The differences in the kinetic parameters fully account for the constancy of uptake rate shown by the germlings.